TOWARDS PROSPEROUS HOUSING: CONSTRUCTION of An ISLAMIC HOUSING CONCEPT WITH A HAYATAN THAYYIBAH PERSPECTIVE - Santoso, Budiyono; Ahmad Jalaluddin; Aunur Rofiq (PT. Altin Riset Publishing, 2024)
Welfare studies are still dominated by materialistic aspects of welfare theory and deny spiritual aspects and spiritual elements. Even though the spiritual aspect is an important thing that influences human life in all aspects. This research aims to explore and develop a concept/model of welfare in housing which was developed based on the Islamic welfare perspective Hayatan Tayyibah. The concept of living well-being Thayyibah is explored using a phenomenological approach, which is a form of design methodology developed based on the Islamic paradigm. Data mining uses interview, observation, and documentation methods. The informants consisted of knowledgeable and experienced informants Data analysis was carried out by describing textural meaning and structural meaning, then carrying out a synthesis to create a universal description of the phenomenon under study. The research findings conclude that the construction of welfare in Islamic housing is referred to as